Analisis Kepribadian Tokoh Reza dalam Novel Pulang ke Rinjani karya Reza Nufa Kajian Psikoanalisis Sigmund Freud - Avieta, Nida Aulia; Baihaqi, Imam; Syahroni, Mashud (Kajian Bahasa dan Sastra (KABASTRA), 2022)
The purpose of this study is to describe the personality of the main character in the novel Pulang ke Rinjani by Reza Nufa based on the id, ego, and superego. This research uses Sigmund Freud's psychoanalytic study. The analytical methods and techniques used are qualitative descriptions using content analysis techniques. The results of this study are to show the personality of the main character in the novel Pulang ke Rinjani by Reza Nufa. Based on the results of data analysis, it was found that there are three personality structures in Reza Nufa's Pulang ke Rinjani Novel, including (1) Reza's personality from the id perspective is more inclined to self-fulfillment to keep achieving the desire for pleasure so that he refuses things that make him feel anxious, one of which is depression. (2) Reza's personality from an ego perspective is more inclined to adjust to the environment that he has never felt before. (3) Reza's personality from the perspective of the superego is more inclined to describe his identity which is in line with the principle of morality based on his conscience. So the superego that happened to Reza was able to grow himself in the order that was formed on the values ​​and norms that prevailed in society. For readers and further researchers in the novel Pulang ke Rinjani by Reza Nufa, there are other aspects that can be studied using theory from a different point of view.